Mekanisme Voice di Pemerintah Kota Yogyakarta (Studi pada Unit Pelayanan Informasi dan Keluhan Kota Yogyakarta) - Try Syeftiani; Boni Saputra (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The Purpose of this study is to describe the voice mechanism in the Yogyakarta City Government, Study of the Information and Complaints Service Unit (UPIK), in the 2013-2019 period. This research uses the Guidelines for Effective Complaint Handling referring to the best practice of the Victorian Ombudsman. The research method used is qualitative with a case study approach. The research results show that UPIK as a Voice Mechanism in the City of Yogyakarta has fulfilled the requirements for an effective complaint handling mechanism. Furthermore, UPIK has succeeded in becoming a forum that functions to accommodate and handle aspirations (complaints) from the people of Yogyakarta City even though there are still messages (complaints) that are in the wrong category and the wrong address, and the City of Yogyakarta's responsiveness is still weak in handling complaints. This is indicated by the fact that there are still complaints that have not been followed up by the relevant SKPD.